Silver nanoparticles and silver salt (AgNO3) elicits morphogenic and biochemical variations in callus cultures of sugarcane. Issue 9 (25th September 2019) - Iqbal, Muhammad; Raja, Naveed Iqbal; Ali, Aamir; Rashid, Hamid; Hussain, Mubashir; Ejaz, Muhammad; Iqbal, Rashid; Khan, Umair A.; Shaheen, Najma; Rauf, Abdul; Satti, Seema Hassan; Saira, Hafiza
Abstract : The research work was arranged to check the role of AgNPs and silver ions on callus cells of sugarcane ( Saccharum spp. cv CP‐77, 400). AgNPs were synthesized chemically and characterized by UV‐Vis spectra, XRD and SEM. AgNPs and silver ions were applied in various concentrations (0, 20, 40, 60 ppm) to sugarcane calli and the induced stress was characterized by studying various morphological and biochemical parameters. AgNPs and silver ions treatments produced high levels of malondialdehyde, proline, proteins, TP and TF contents. Similarly, CAT, SOD and POX activity was also significant in both treatments. The lower concentration of AgNPs and silver ions (20 ppm) provided maximum intracellular GSH level. This work mainly showed effects of AgNPs and silver ions on sugarcane calli in terms of morphological aberrations and cell membrane damage due to severe oxidative stress and production of enhanced levels of enzymatic and non‐enzymatic antioxidants as self‐defence to tolerate oxidative stress by scavenging reactive oxygen species. These preliminary findings will provide the way to study ecotoxicity mechanism of the metal ions and NPs in medicine industry and in vitro toxicity research. Furthermore, silver ions alone and their chemically synthesised AgNPs can be used for various biomedical applications in future.